New political parties through the voters' eyes - Wuttke, Alexander (2019)
Abstract: Scholars mainly studied the formation of political parties on the macro-level, but to explain the conditions of successful party establishment we need to understand the motivational underpinnings of voting for a new party on the individual level. Using cross-national voter surveys and long-term panel data from Germany (2005-2013) and the Netherlands (1998-2002), this study contrasts the implicit assumptions about voter behaviour of equilibrium- and protest-based theories on party emergence. Although proximity to a new party matters, the findings do not support the equilibrium perspective’s tenet that new parties gain votes from citizens whose views were not represented in the preceding election. Moreover, political discontent was found a fertile soil for new parties to gain electoral support, but the relationship between discontent and voting is more complex than theoretically suggested. These findings on individual voter behaviour may inform further theoretical work on the success